Preparation for Independent Life of People with ASD and Other Developmental Disorders in The Autonomous Noncommercial Organization «Adain Lo» (ANO «Adain Lo») - Ginsburg A.A; Gitshabash M.E; Ivanova Ya.L (Moscow State University of Psychology and Education, 2018)
The problems of preparation of children and adults with autism spectrum disorders and other developmental disabilities for independent life, modern ways of development of their independence are considered. The role of parents in this process and parent-specialist interaction are stressed. The techniques of tutor support, parents and other specialists are described. Presented techniques are realized in autonomous non-commercial organization «Adain Lo» (Saint-Petersburg) and aimed for maintenance of independent life, self-service, game, communication and education of people with special needs.